Prognostic value of local relapse for patients with endometrial cancer. Issue 11 (November 2017) - Dabi, Y.; Uzan, J.; Bendifallah, S.; Ouldamer, L.; Lavoué, V.; Canlorbe, G.; Raimond, E.; Coutant, C.; Graesslin, O.; Collinet, P.; Bricou, A.; Daraï, E.; et al.
Abstract: Background: The objective of our study was to determine survival and prognostic factors associated with isolated local recurrence of endometrial cancer. Methods: Data of 1229 patients with endometrial carcinoma treated between 2000 and 2012 were extracted from maintained databases of nine French University Hospitals as well as from the Senti-Endo trial. Patients with isolated central pelvic and vaginal recurrence were selected for further analysis. Results: Two hundreds and twenty five patients recurred during the inclusion period, 20 with isolated central pelvic recurrence and 23 with vaginal recurrence. Patients without recurrence had initially significantly less lymphovascular space invasion (p = 0.01), less advanced diseases (>stage II) (p < 0.001) and more often low or intermediate risk tumours than patients with local recurrence. Local recurrence was statistically associated with better overall survival than non-local recurrence (p = 0.028) but dramatically decreased overall survival when compared to patients without any recurrence (p < 0.001). The site of recurrence, i.e. vaginal or central pelvic, was significantly associated with overall survival (p = 0.015). Patients without brachytherapy at initial management were more likely to have local recurrence of their disease when compared to those without recurrence (p = 0.03). None of the prognostics factors for survival in patients with local recurrence was statistically significant in multivariate analysis. Conclusions: Local recurrence is a key event in endometrial cancer evolution severely impacting overall survival. Better understanding of the factors associated with prolonged survival is mandatory to improve our management of these patients.